1991
DOI: 10.1128/aem.57.3.775-784.1991
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Water Column Acidification on Protozoan Bacterivory at the Lake Sediment-Water Interface

Abstract: Although the impact of acidification on planktonic grazer food webs has been extensively studied, little is known about microbial food webs either in the water column or in the sediments. Protozoon-bacterium interactions were investigated in a chronically acidified (acid mine drainage) portion of a lake in Virginia. We determined the distribution, abundance, apparent specific grazing rate, and growth rate of protozoa over a pH range of 3.6 to 6.5. Protozoan abundance was lower at the most acidified site, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 63 publications
(80 reference statements)
0
3
0
1
Order By: Relevance
“…The results of our small-scale experiments suggest that microfaunal organisms in an activated sludge wastewater treatment system may be able to survive at low pH levels of 4.5 to 5.5, that is, below the stated optimum of pH 6.5 to 8.0 (Benefield andRandall 1988, Pennak 1989). Similarly, in an acidified lake with a pH range of 3.6 to 6.4, Tremaine and Mills (1991) found protozoan abundance to be highest at pH 5.0 to 5.3. However, the temperature of the sludge environment in wastewater treatment is also an important factor to consider.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The results of our small-scale experiments suggest that microfaunal organisms in an activated sludge wastewater treatment system may be able to survive at low pH levels of 4.5 to 5.5, that is, below the stated optimum of pH 6.5 to 8.0 (Benefield andRandall 1988, Pennak 1989). Similarly, in an acidified lake with a pH range of 3.6 to 6.4, Tremaine and Mills (1991) found protozoan abundance to be highest at pH 5.0 to 5.3. However, the temperature of the sludge environment in wastewater treatment is also an important factor to consider.…”
Section: Discussionmentioning
confidence: 86%
“…Given the complex organic nature of the activated sludge, a wide range of buffering reactions might be involved. Tremaine and Mills (1991) suggested that anaerobic microbial reduction of iron and sulfate might buffer pH in lake sediments, sufficient to maintain a neutrophilic protozoan community.…”
Section: Discussionmentioning
confidence: 99%
“…The protozoan community from an acidified station (sediment-water interface of an acid mine drainage) was not better adapted to low-pH conditions than a community from an unacidified site. 80 The sed-iment buffering was probably sufficient to maintain a neutrophilic protozoan community.…”
Section: Effecfs On Tolerancementioning
confidence: 99%
“…Associado ao fluxo de biomassa, os protozoários bacterívoros tem se mostrado eficientes mineralizadores de nitrogênio e fósforo, reciclando o carbono e os nutrientes via cadeia alimentar microbiana, sendo especialmente importantes em ecossistemas pobres em nutrientes, como os ambientes oligotróficos, onde as interações tróficas estão tensamente relacionadas (TREMAINE;MILLS, 1991;GONZÁLEZ, 1999;SIMEK et al 2001).…”
Section: Protozooplâncton E Relações Com Outras Populações Microbianaunclassified